2018
DOI: 10.31540/jpm.v1i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Pemanfaatan Media Sosial Edmodo Sebagai Media Pendukung Pembelajaranbagi Guru Di SMP Tamansiswa Palembang

Abstract: Media sosial yang mempunyai banyak manfaat dalam pembelajaran adalah Edmodo. Edmodo adalah media sosial yang berdasarkan pada lingkungan sekolah (school based environment). Edmodo merupakan media sosial yang bisa dimanfaatkan oleh guru, siswa dan orang tua siswadi kelas pada suatu sekolah. Edmodo memberikan cara yang mudah untuk berhubungan antara guru dan siswa, maupun antara guru dan orang tua siswa sehingga menciptakan interaksi yang kuat dan memudahkan dalam berkomunikasi tanpa harus bertatapan langsung. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…However, it can be a forum for sharing with teachers to develop learning methods that have been applied. Strengthened by Yenni & Malalina (2018), The results of this study found that the retention value of students who were taught with the Edmodo-based Blended Learning model was significantly higher than those conducted by the direct learning model. This is because Edmodo's learning makes learning not dependent on time and place and makes the classroom more dynamic because it allows the interaction of teachers with students and between students and students in terms of lessons or assignments.…”
Section: Resultsmentioning
confidence: 71%
“…However, it can be a forum for sharing with teachers to develop learning methods that have been applied. Strengthened by Yenni & Malalina (2018), The results of this study found that the retention value of students who were taught with the Edmodo-based Blended Learning model was significantly higher than those conducted by the direct learning model. This is because Edmodo's learning makes learning not dependent on time and place and makes the classroom more dynamic because it allows the interaction of teachers with students and between students and students in terms of lessons or assignments.…”
Section: Resultsmentioning
confidence: 71%
“…Pada saat ini, para pelajar baik siswa maupun mahasiswa sudah banyak yang menggunakan computer network atau internet dalam proses pembelajaran. sebelumnya siswa hanya menggunakan buku sebagai sumber belajar, tetapi sekarang berbagai materi pelajaran bisa mereka jumpai pada media berbasis internet, sehingga mereka tidak hanya membaca tulisan yang ada pada buku pelajaran, tetapi juga menemukan beragam informasi yang ada pada internet (Yenni 2018). Tetapi disisi lain, penggunaan internet oleh peserta didik khususnya di kabupaten Ogan Komering Ulu (OKU) banyak disalah gunakan seperti membuka situs-situs jejaring sosial, terlalu banyak chatting, facebook, bermain game online, dan mengakses pornografi yang jelas kurang bermanfaat.…”
Section: Pendahuluanunclassified